Integrated Skills Approach in Teaching EFL Writing and Speaking as Productive Skills: A Case Study in Indonesian Context - Dewi, Melawati; Muslim, Ahmad Bukhori (LET: Linguistics, Literature and English Teaching Journal, 2024)
Teaching English as Foreign Language to Indonesian students encourages teachers to motivate them in their language study by getting them to engage in successful writing and speaking skills. It can be early learning as relevant as possible to their language use needs. Based on a qualitative design, this study investigated the way an English teacher of eleventh-grade students used an integrated skills approach to teaching writing and speaking in the classroom.  The research was conducted at one of the senior high schools in West Java, Indonesia with a qualitative method to explore deep information about the strategies and challenges encountered by the English teacher when she was teaching. The specific strategy revealed that the teacher organized activities and encouraged the students through Communicative Language Teaching (CLT) including other strategies to overcome the challenges such as providing consultation and providing learning at night as an extra class. This study is expected to chronicle the need for this approach to be incorporated by English teachers in secondary schools to improve English teaching strategy today and future.